2006
DOI: 10.1289/ehp.9165
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of Early Life Environmental Tobacco Smoke Exposure: Early Intervention for Developmental Delay

Abstract: Background and ObjectivesEarly-life exposure to environmental tobacco smoke (ETS) can result in developmental delay as well as childhood asthma and increased risk of cancer. The high cost of childhood asthma related to ETS exposure has been widely recognized; however, the economic impact of ETS-related developmental delay has been less well understood.Methods and ResultsThe Columbia Center for Children’s Environmental Health (CCCEH) has reported adverse effects of prenatal ETS exposure on child development in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
0
17
0
2
Order By: Relevance
“…For instance, Olds et al [99] found that smoking 10 or more cigarettes per day during pregnancy was associated with a 4.35 point decrease in Stanford-Binet intelligence quotient (IQ) scores of offspring. At the societal level, Miller et al [102] estimate that the annual cost of early intervention services attributable to SHS exposure for New York City alone is approximately US$99 million.…”
Section: Cognitive Impairmentsmentioning
confidence: 99%
“…For instance, Olds et al [99] found that smoking 10 or more cigarettes per day during pregnancy was associated with a 4.35 point decrease in Stanford-Binet intelligence quotient (IQ) scores of offspring. At the societal level, Miller et al [102] estimate that the annual cost of early intervention services attributable to SHS exposure for New York City alone is approximately US$99 million.…”
Section: Cognitive Impairmentsmentioning
confidence: 99%
“…One of the most prevalent and significant global chemical exposures is cigarette smoke, which places a substantial medical and financial burden on public health systems worldwide. [1][2][3] Cigarette smoking (including passive smoking) has adverse effects on a wide range of organ systems, leading to pulmonary and cardiovascular disorders and problems with human fertility, reproduction and early development. 1,4,5 Perhaps even more worryingly, two of the constituents of cigarette smoke, benzo[a]pyrene and nicotine, have recently been shown to induce harmful phenotypes that can be transmitted through the mammalian germ line to future generations.…”
Section: Introductionmentioning
confidence: 99%
“…This reflects the reduction in exposure to SHS that has occurred in California over the last few decades. Four other studies of healthcare costs resulting from childhood SHS exposure also are based on much higher exposure rates than those in California: a New York City study of developmental delay used prenatal exposure of 40%,10 a national study of respiratory illness used 25–30% exposure (depending on age),21 a study of childhood illness in the state of Maine was based on exposure rates from pregnant mothers smoking of 26%22 and a study of SHS-attributable costs for all US children under age 18 used a maternal smoking while pregnant rate of 28% and an exposure rate for children of 42% 23. Third, the study by Adams and colleagues9 did not limit their estimate to specific diseases that are causally linked with exposure to maternal smoking in utero; rather they compared the probability of being admitted into the neonatal intensive care unit (NICU) for any reason, and the length of stay in the NICU for those newborns admitted, between exposed and unexposed newborns.…”
Section: Discussionmentioning
confidence: 99%
“…One study that estimated total annual SHS-attributable costs for the USA reported medical costs of $6.9 billion 8. Other studies have focused on children, including the impact of exposure in utero due to smoking by the mother9 10 and the impact of exposure on children from parental smoking and living with smokers 11. Many of these studies also estimated the value of lives lost prematurely from SHS-attributable illness 4 7 8.…”
mentioning
confidence: 99%